Effect of Fluorinated Comonomer, Polymerizable Emulsifier, and Crosslinking on Water Resistance of Latex Coatings - Machotová, Jana; Knotek, Petr; Černošková, Eva; Svoboda, Roman; Zarybnicka, Lucie; Kohl, Miroslav; Kalendová, Andréa (MDPI, 2022)
Common latex coatings suffer from poor water resistance, which often limits their practical application. This paper reports on the preparation of polyacrylate latexes using various approaches to tune the water resistance, wettability, and surface properties of their coating films. The mutual effects of fluorinated monomer copolymerization, emulsifier type (polymerizable and general), and intra- or interparticle covalent crosslinking (due to allyl methacrylate copolymerization and a keto-hydrazide reaction, respectively) were studied. The polyacrylate latexes were synthesized through a two-step semicontinuous emulsion polymerization of 2,2,2-trifluoroethyl methacrylate, butyl acrylate, methyl methacrylate, and methacrylic acid as the basic monomers. The fluorinated monomer was incorporated into the second-step polymer (at a content of 30 wt.% based on the second-step monomer feeds). The water resistance, wettability, and surface properties of the coating films were evaluated with focus on the water absorption, water whitening, water contact angle, and surface topography using atomic force microscopy. It was found that highly water-resistant and hydrophobic coatings that possessed a self-healing ability were prepared, provided that the polymerizable emulsifier and the fluorinated monomer were involved in the latex synthesis, along with the intra- and interparticle covalent crosslinking.
Vliv fluorovaného komonomeru, polymerovatelného emulgátoru a síťování na odolnost latexových nátěrů vůči vodě
Keywords: polyacrylate latex; polymerizable emulsifier; crosslinking; keto-hydrazide reaction; water resistance; hydrophobicity; self-healing; akrylátový latex; síťování; keto-hydrazidová reakce; polymerizovatelný emulgátor; voděodolnost; hydrofobnost; self-healing